2022
DOI: 10.1039/d2qi00863g
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling the degradation mechanism for the hydrogen storage property of Fe nanocatalyst-modified MgH2

Abstract: Maintaining fast hydrogen storage kinetics is a key challenge for the practical application of MgH2. To address this challenge, understanding the mechanism of kinetics declining during cycling is crucial but...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(6 citation statements)
references
References 60 publications
0
6
0
Order By: Relevance
“…As shown in Figure a, even after 50 cycles of hydrogen absorption at 150 °C and desorption at 275 °C, the MgH 2 –5 wt % Ni@C composite exhibited excellent reversibility, and the total capacity decay for hydrogen absorption and desorption was only 2.9 and 5.6% after 50 cycles, respectively. Compared with other MgH 2 –catalyst composites, ,,, the MgH 2 –5 wt % Ni@C composite in this work exhibits superior cycling stability. We observed the microstructure and phase composition of the MgH 2 –5 wt % Ni@C composite before and after hydrogen absorption/desorption cycling.…”
Section: Resultsmentioning
confidence: 99%
“…As shown in Figure a, even after 50 cycles of hydrogen absorption at 150 °C and desorption at 275 °C, the MgH 2 –5 wt % Ni@C composite exhibited excellent reversibility, and the total capacity decay for hydrogen absorption and desorption was only 2.9 and 5.6% after 50 cycles, respectively. Compared with other MgH 2 –catalyst composites, ,,, the MgH 2 –5 wt % Ni@C composite in this work exhibits superior cycling stability. We observed the microstructure and phase composition of the MgH 2 –5 wt % Ni@C composite before and after hydrogen absorption/desorption cycling.…”
Section: Resultsmentioning
confidence: 99%
“…Later, Zhang et al [ 82 ] found that iron nanosheets (Fe NS) led to better dehydrogenation/rehydrogenation kinetics of Mg/MgH 2 compared to iron particles. Recently, Song et al [ 93 ] introduced Fe nanocatalysts into MgH 2 and found that the operating temperature and activation energy of MgH 2 was significantly reduced. However, the growth of grains in Mg/MgH 2 -Fe composites during the dehydrogenation/rehydrogenation cycle resulted in capacity loss and kinetic degradation.…”
Section: Improvement Of Hydrogen Storage Performance Of Mg/mgh ...mentioning
confidence: 99%
“…Besides the 2D grain boundaries, the large density of 1D lattice defects, such as dislocations, created by HEBM can further promote hydrogen sorption due to the enhanced diffusion length of hydrogen [34,35]. The catalytic effect of various additives, such as transition metals [36][37][38][39][40], metal oxides [32,[41][42][43][44][45], and carbonbased materials [46][47][48] incorporates an easier H 2 molecule dissociation at the surface of the nanoparticles, resulting in the reduction in hydride formation enthalpy. The hydriding reaction of Mg-based materials with hydrogen includes several stages, such as (I) Physisorption of the H 2 molecules by weak van der Waals interaction onto the free surface of magnesium powder particles; (II) Dissociation of hydrogen molecules into two H atoms; (III) Chemisorption of hydrogen atoms; (IV) Diffusion into bulk lattice sites, preferably along grain boundaries and dislocations and as a final step; (V) The nucleation and growth of the MgH 2 takes place [23,49].…”
Section: Introductionmentioning
confidence: 99%